2007
DOI: 10.4049/jimmunol.179.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Memory Generation and Maintenance of CD8+ T Cell Function during Viral Persistence

Abstract: During infection with viruses that establish latency, the immune system needs to maintain lifelong control of the infectious agent in the presence of persistent Ag. By using a γ-herpesvirus (γHV) infection model, we demonstrate that a small number of virus-specific central-memory CD8+ T cells develop early during infection, and that virus-specific CD8+ T cells maintain functional and protective capacities during chronic infection despite low-level Ag persistence. During the primary immune response, we show gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 102 publications
7
41
0
Order By: Relevance
“…It should also be noted that during late latency, the percentage of specific lysis in vivo in the absence of CD8 T cells increases modestly, from 12% to 23%, as latent infection progresses (Fig. 3C), which is in stark contrast to the pattern of CD8 T-cell-mediated cytotoxicity, which peaks early during infection and is followed by a dramatic reduction by 3 months postinfection (6,16). These experiments indicate that CD8 T cells do not make a significant contribution to the killing of ␥HV68-loaded targets during an in vivo cytotoxicity assay.…”
mentioning
confidence: 54%
“…It should also be noted that during late latency, the percentage of specific lysis in vivo in the absence of CD8 T cells increases modestly, from 12% to 23%, as latent infection progresses (Fig. 3C), which is in stark contrast to the pattern of CD8 T-cell-mediated cytotoxicity, which peaks early during infection and is followed by a dramatic reduction by 3 months postinfection (6,16). These experiments indicate that CD8 T cells do not make a significant contribution to the killing of ␥HV68-loaded targets during an in vivo cytotoxicity assay.…”
mentioning
confidence: 54%
“…Unlike naive T cells, homeostasis of memory CD8 + T cells occurs independently of antigen and MHC-I and utilizes cytokines IL- 7 and IL-15 (14,15,(18)(19)(20)(21). It has been suggested that persisting antigen might help sustenance of effector and memory CD8 + T cells (36,37). Thus, it was possible that homeostatic maintenance of helpless antifungal memory CD8 + T cells benefited from the presence of persisting vaccine antigen in our model.…”
Section: Discussionmentioning
confidence: 85%
“…Limited TCR stimulation by self antigens could also play a role, as memory T cells that receive constant stimulation by exogenously administered foreign peptide antigen become impaired in their tumoricidal function (40). Alternatively, memory in vitiligo-affected mice may more closely resemble responses in hosts with chronic gammaherpesvirus or Trypanosoma cruzi infection, wherein T cells maintain an effector memory phenotype, resist functional exhaustion (41), and can provide protection in the face of persisting antigen (42)(43)(44). While classical T EM cells are thought to convert to T CM cells with time (45), the ontogeny of vitiligo-associated memory T cells remains unclear, although a small T CM population may play a role in maintaining the response.…”
Section: Figurementioning
confidence: 99%